ANALYSIS OF FACTORS THAT INFLUENCE BEHAVIOR, MOTIVATION AND TRAINING OF MIDWIFE ON THE IMPLEMENTATION OF INITIATION EARLY BREASTFEEDING (IMD) AT RSU ROYAL PRIMA MEDAN - raflesia, yoshine (Public Health Faculty, Universitas Diponegoro, 2020)
Based on the results of evaluations conducted at RSU Royal Prima Medan, there were still midwives who had not implemented IMD. This study aims to look for the Effect of Knowledge, Length of Work, Motivation and Training on the Implementation of Early Breastfeeding Initiation.Research is analytic observational. This research was conducted at RSU Royal Prima Medan in February to March 2019. Samples were taken using proportional stratified random sampling technique, namely 30 people. Data collected by distributing questionnaires. Data processing using SPSS.The results of this study indicate the duration of work P-value 0.008 means that there is an influence between the length of work with the implementation of early breastfeeding initiation and motivation P-value 0.005 means that there is a distinction between moivation, implementation of early initiation initiation and training of P-value 0.008 means that there is an influence between implementation of early breastfeeding initiation with training. Midwives are expected to attend training to improve performance.